Nutrição mineral, produção, qualidade e análise econômica do abacaxizeiro cv. Pérola, em função das relações K/N - Rodrigues, Alessandra Alves (2009)
The management of the pineapple plant fertilization requires the applications of N and K at high doses, besides the establishment of appropriate relationships among them. This study was conducted to evaluate the effect of the different K/N relationships on the mineral nutrition, yield and quality of the pineapple fruits 'Pérola'. The experiment was carried out in a low fertile and sandy-textured Espodossolo Ferrocárbico at Santa Rita county of Paraíba State, during the period from March 2006 to September 2007. The randomized block experimental design was adopted, with three replicates. The slip type suckers were planted at spacing 0.80 × 0.30 m under simple row system. Thirteen treatments resulting from four relationships K/N (0.85:1; 1:1; 2:1 and 3:1) generated from two N doses, as being one considered low (7.2 g/plant N) and another high (10.8 g/plant N) were evaluated. Other four additional treatments (source, plotting, time and the application form of the potassium fertilizer) and control (without fertilization). At 0-20cm depth of the soil, the following variables were determined: pH and contents of the organic matter, P, K, Ca, Mg and Al. At 120, 240 and 330 days after planting, the leaf contents of N, P, K, Ca, Mg and S were determined and the values of the relationships K/N, K/Ca and K/Mg were estimated. The harvest was accomplished at 17 months after planting and the following variables were evaluated: average weight of the fruits, total productivity and percent fruits of the classes I (0.8-1.2 kg), II (1.20- 1.50 kg) and III (1.51-1.80 kg). Concerning to quality, the following characteristics were determined in the fruits pertaining to classes I and II: length and average diameter; length and weight of the crown; weights of the husk, of the pulp and of the stem; pH, soluble solids (obrix), titrable acidity and relationship SS/AT . The evaluation of the economical viability of the treatments were based on the cost/benefit relationship (C/B). The results showed that the K/N relationships and the additional treatments did not affect the attributes of soil fertility, except for the contents of K and S. The K/N relationships did not affect the weight of the 'D' leaf neither the leaf contents of N, P, K, Ca and Mg in the samplings accomplished at four, eight months and at the floral induction time. They also did not affect the average weight, the productivity and the percent fruits pertaining to classes I, II and III. Higher N doses (450 kg/ha) increased the average weight, total productivity and the percent fruits of the classes II and III, but reduced the percent fruits of the class I. The K sulfate increased either average weight and percent fruits of the class III, whereas the N and K doses from which half was applied on the soil and half through leaf rather increased the productivity of fruits. The K/N relationships did not affect the quality attributes of the fruits, although the N and K applications after floral induction and that of K sulfate reduced the acidity of the fruits. The use of the K sulfate resulted into higher gross revenue and higher additional value, although the highest B/C relationship was obtained with the application of half doses on the soil and half ones via leaf (R$ 1,46).